Experimental Investigation of the Effect of Temperature on Biodiesel Production from Used Cooking Oil - Prasetiyo, Dani Hari Tunggal; Ilminnafik, Nasrul; Sanata, Andi; Sholahuddin, Imam; Arbiantara, Hari; Dwilaksana, Dedi (Journal of Earth Energy Science, Engineering, and Technology, 2026)
Used cooking oil is a waste product with great potential as a raw material for biodiesel production through transesterification. This study was conducted to determine the effect of transesterification reaction temperature on biodiesel yield and quality. The biodiesel production process includes a degumming step to remove gums by adding 1% H₃PO₄. This is then followed by transesterification using 1% NaOH as the catalyst, an oil-to-methanol ratio of 1:0.5, a stirring speed of 300 rpm, and a reaction time of 60 minutes. The transesterification reaction temperatures were 40°C, 50°C, 60°C, and 70°C. The results showed that the reaction temperature significantly affected the yield and physical quality of biodiesel. The highest yield was 85.85% at 40°C, while the lowest was 80.37% at 70°C. The maximum viscosity was observed at 60°C (6.0 cSt), and the minimum at 70°C (5.71 cSt). The highest density was 0.8620 g/mL at 50 °C, and the lowest was 0.8607 g/mL at 40 °C. The highest flash point was 40°C at 173.27°C, and the lowest was 70°C at 164.97°C. The results showed that the biodiesel produced met the quality standards of SNI 7182:2015, thus supporting its suitability as an alternative fuel derived from used cooking oil.